Superior efficacy of calcipotriene and betamethasone dipropionate aerosol foam versus ointment in patients with psoriasis vulgaris – A randomized phase II study. (3rd March 2016) - Koo, John; Tyring, Stephen; Werschler, William P.; Bruce, Suzanne; Olesen, Martin; Villumsen, John; Bagel, Jerry
Abstract: Background : An aerosol foam formulation of fixed combination calcipotriene 0.005% (as hydrate; Cal) plus betamethasone dipropionate 0.064% (BD) was developed to improve psoriasis treatment. Objectives : To compare the efficacy and safety of Cal/BD aerosol foam with Cal/BD ointment after 4 weeks. Methods : In this Phase II, multicenter, investigator-blind, 4-week trial, adult patients with psoriasis vulgaris were randomized to Cal/BD aerosol foam, Cal/BD ointment, aerosol foam vehicle or ointment vehicle (3:3:1:1). The primary efficacy endpoint was the proportion of patients at week 4 who achieved treatment success (clear or almost clear with at least a two-step improvement) according to the physician's global assessment of disease severity. Results : In total, 376 patients were randomized. At week 4, significantly more patients using Cal/BD aerosol foam achieved treatment success (54.6% versus 43.0% [ointment]; p  = 0.025); mean modified (excluding the head, which was not treated) psoriasis area and severity index score was significantly different between Cal/BD aerosol foam and Cal/BD ointment (mean difference –0.6; p  = 0.005). Rapid, continuous itch relief occurred with both active treatments. One adverse drug reaction was reported with Cal/BD aerosol foam (application site itch). Conclusions : Cal/BD aerosol foam demonstrates significantly greater efficacy and similar tolerability compared with Cal/BD ointment for psoriasis treatment.